The study of the composition of the natural nanostructured material - chrysotile asbestos - Medetov, N.A. (Publishing House of the KarSU named after E.A.Buketov, 2012)
The article discusses the properties of the natural nanostructured material - chrysotile asbestos. The object of the research is produced at the minefield in Zhitikara, Kostanai region. Some areas for possible application of asbestos as a material consisting of nanotubes are offered. Chrysotile fiber has been tested by means of X-ray techniques, including X-ray diffraction and small-angle scattering measurement. The experiments are based on the use of X-ray multifunctional processor.
Keywords: chrysotile asbestos; nanotubes; X-ray analysis techniques